Strategic Management of Educators and Education Personnel at Vocational High Schools in Samarinda City - Harliansyah, Harliansyah (PT Literasi Nusantara Publisher, 2022)
This paper aims to describe the strategic management of educators and education personnel at SMK Negeri 9 Samarinda. This study uses qualitative research methods and SWOT analysis. The results of this study indicate that the strategic management of educators and education personnel is carried out based on statutory regulations with the aim of improving the quality of national education, developing science, technology, and art, as well as serving the community. The implementation of the duties and functions of educators and education management consists of six components, namely: (a) planning, (b) recruitment, (c) job placement, (d) compensation, (e) coaching and development, (f) evaluating. The functions and duties of management have implications for schools in facing a shortage of educators and education personnel. Guidance and development are also carried out through individual learning, training and advanced education, whether carried out by working groups of teachers, schools, or the education office.